Preliminary Pharmacological Studies of Methanolic Extract of Cryptolepis buchanani Leaves (Bangladesh Pharmaceutical Journal, 2025)
The purpose of this study is to assess the characteristics associated with the depressive, anxiolytic, analgesic and thrombolytic activities of the methanolic extract of Cryptolepis buchanani leaves. The writhing test (acetic acid-induced), paw licking test (formalin-induced), tail suspension test (TST), forced swim test (FST), elevated plus maze test (EPM), and hole board test (HBT) were utilized to assess the in-vivo analgesic, anxiolytic, and antidepressant effects. An in-vitro human blood clot lysis method was also used to test the thrombolytic activity. In animal models, the tail suspension test (TST) and the forced swim test (FST) resulted in a shorter immobility time. The methanolic extract of C. buchanani (MECB) was administered at doses of 200 and 400 mg/kg, resulting in a dose-dependent increase in the mice's mobility duration. In both the Elevated Plus Maze (EPM) and the Hole Board Test (HBT), mice were given varying doses of MECB. Shortly after administration, the EPM results showed that the mice spent more time in the open arms and dipped their heads more frequently. The mice's writhing frequency and licking duration were significantly reduced, indicating an analgesic effect throughout the test. For each dose tested, the response varied as the concentration increased. This study concludes that the extract has anxiolytic, antidepressant, analgesic and thrombolytic properties, supporting the plant's traditional use in medicine.Bangladesh Pharmaceutical Journal 28(2): 164-174, 2025 (July)